Drawing the Surface of Dance : A Biography in Charts - Parson, Annie-B (Book collections on Project MUSE., 2019)
"Soloing on the page, choreographer Annie-B Parson rethinks choreography as dance on paper. Parson draws her dances into new graphic structures calling attention to the visual facts of each dance work she has made. These drawings serve as both maps of her pieces in the aftermath of performance, and as a consideration of the elements of dance itself. Within the duality of form and content, this book explores the meanings that form itself holds. Parson's charts of choreaographic ideas inspire new thinking around the shared elements underneath all art making."--Page [4] of cover.